Blue-light-blocking films enabled by optimal absorption in plasmonic nanoparticles. (1st January 2023) - Chu, Bo; Zhong, Facheng; Hu, Taozheng; Li, Yan; Yan, Rujiang; Shao, Li; Zeng, Fanguang; Ding, Pei; Du, Yinxiao; Gu, Ping; Wang, Junqiao; Chen, Zhuo
Abstract: The widespread use of light emitting diode (LED) based devices makes us inevitably exposed to a blue-enriched environment and brings a potential risk to our eyes. Developing a blue-light-blocking filter with narrow absorbing band, so as to only block harmful blue light (415–455 nm) is highly expected. Here, we create a blue-light-blocking film, consisting of a transparent medium embedded with plasmonic nanoparticles (NPs) that selectively absorb harmful blue light. We present the optimal design based on Mie theory by comprehensive scanning of the parametric space for the NPs, and experimentally demonstrate this concept with a blue-light-blocking film made of silver NPs in a polymer matrix by a simple solvothermal method. For the case of the silver NPs content ∼0.16 wt%, the film can block harmful blue light ∼65% at λ 0 ≈ 430 nm, while maintaining high transparency for the long wavelength light ( λ 0 > 500 nm). We also demonstrate that it is possible to correct color cast by optimizing the design of the plasmonic NPs with sharp absorption resonances at yellow waveband. This method has attractive features including simplicity, low cost, non-toxic and scalability to large sizes, which makes it beneficial for blue-light-blocking applications.